2018
DOI: 10.15419/bmrat.v5i10.490
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Matricaria chamomilla L.hydroalcoholic extract on atherosclerotic plaques, antioxidant activity, lipid profile and inflammatory indicators in rats

Abstract: Introduction: Treatment of cardiovascular risk factors seems to be necessary and involves a number of changes in drug treatment and lifestyle. This study aimed to evaluate the effects of Matricaria chamomilla L. hydroalcoholic extract on antioxidant activity, atherosclerotic plaques, lipid profile and inflammatory indicators in rats. Methods: Thirty male Wistar rats were divided into five experimental groups consisting of group 1 (Sham; normal dietary), group 2 (control; high cholesterol diet (2%)), grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…Similarly, Rafraf et al (2015) reported that chamomilla extract as a natural material, decreasing of blood cholesterol by two pathways by the presence of flavonoids that enhance the phosphorylation of Hydroxy-methylglutaryl-CoA (HMG CoA) reductase enzyme indirectly thus diminish endogenous cholesterol production, Also, Iweala and Oludare, (2011) concluded that rosemary had a hypolipidemic effect due to the antioxidant effect of its constituents, which changed the rate of fatty acids oxidation in the liver and reduced the rate of triglycerides biosynthesis and reduced the rate of triglycerides biosynthesis in rats. Similar results of reduction in cholesterol and triglyceride concentrations due to chamomile and rosemary supplementation were reported by Gupta and Misra (2006); Nargesi et al (2018) and Gabr (2016).…”
Section: Blood Constituentssupporting
confidence: 85%
“…Similarly, Rafraf et al (2015) reported that chamomilla extract as a natural material, decreasing of blood cholesterol by two pathways by the presence of flavonoids that enhance the phosphorylation of Hydroxy-methylglutaryl-CoA (HMG CoA) reductase enzyme indirectly thus diminish endogenous cholesterol production, Also, Iweala and Oludare, (2011) concluded that rosemary had a hypolipidemic effect due to the antioxidant effect of its constituents, which changed the rate of fatty acids oxidation in the liver and reduced the rate of triglycerides biosynthesis and reduced the rate of triglycerides biosynthesis in rats. Similar results of reduction in cholesterol and triglyceride concentrations due to chamomile and rosemary supplementation were reported by Gupta and Misra (2006); Nargesi et al (2018) and Gabr (2016).…”
Section: Blood Constituentssupporting
confidence: 85%
“…After 10 days, the hyperlipidemic mice treated orally with 6% of chamomile (4 mg/kg) had significantly reduced serum cholesterol compared with control rats. Same results stated by Shahin et al, (2018) who found that treatment of hypercholesterolemic rats with 110 mg/kg of chamomile extract for 4 weeks did not only prevent a significant increase of triglycerides, cholesterol, and inflammatory factors, but it also increase antioxidant enzyme. Mansour et al, (2018) reported the oxidative damage induced by a high cholesterol (2%) diet is modulated by consumption of herbal extracts like 55 mg/ml chamomile and it can be said that to minimize the damages caused by 10 mg/kg b.w of lovastatin drug.…”
Section: Discussionsupporting
confidence: 65%
“…chamomilla EOs and extracts possess antioxidant activity that allows their use to prevent or treat diseases. In male Wistar rats, the intake of hydroalcoholic extract prevented the increase of superoxide dismutase globule and plasma malondialdehyde caused by a high cholesterol diet [125]. Additionally, in diabetic rats, the treatment with 10 and 20% M. chamomilla powder significantly decreased lipid peroxidation and increased catalase, acetylcholine esterase, and glutathione levels in serum [19].…”
Section: Pharmacological Interest 41 Antioxidant Activitymentioning
confidence: 93%
“…They also had a significant inhibitory effect on the increase in prostaglandin E2 and nitric oxide levels in rat pedal edema caused by carrageenan [168]. Furthermore, the effects of M. chamomilla hydroalcoholic extract on the level of inflammatory blood indicators were investigated on rats by Nargesi et al [125]. Treatment with 110 mg/kg hydroalcoholic extract prevented a significant increase in serum levels of Tumor Necrosis Factor-α (TNF-α), C-Reactive Protein (CRP), Interleukin 6 (IL-6), and fibrinogen.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%